Effect of Injectable Bone Substitute Preparation Formulation on Microscopic and Macroscopic Characteristics for Bone Graft - Alaydrus, M. Mukaddam; Rahayu, Susi; Purnaning, Dyah; Isa A.A, Maz; Oktri P, Awanda; Taufik S, Ahmad (Jurnal Ilmiah Farmako Bahari, 2025)
Biocompatible, mechanically stable, and easy-to-use injectable biomaterials are often needed for bone defects caused by trauma, disease, or surgery. This study aims to investigate the effect of polyvinyl alcohol (PVA) concentration on the microscopic and macroscopic characteristics of injectable bone substitute (IBS) formulations composed of Hydroxyapatite (HAp), chitosan, and PVA. The biopolymer chitosan was extracted from pearl oyster shell waste (Pinctada maxima), and HAp was synthesized via precipitation. The formulations were prepared with varied PVA concentrations (5%, 10%, and 15%) and evaluated for their structural, physicochemical, and functional properties. Fourier-transform infrared (FTIR) spectroscopy was employed to determine the presence of functional groups and molecular interactions. Results showed that increasing PVA content enhanced the intensity and sharpness of phosphate () bands, with Sample C (15% PVA) exhibiting the strongest interaction, indicated by a peak shift to 1047.32 cm⁻¹. Organoleptic observations revealed stable color across all samples, with increasing viscosity and paste-like consistency observed in higher PVA concentrations. Sample C had the highest viscosity (82.2 dPa·s) and the lowest injectability (92.43%), while Sample A exhibited the highest injectability (98.33%) and the lowest viscosity (2.79 dPa·s). Sample B (10% PVA) showed balanced characteristics with a viscosity of 38.93 dPa·s and injectability of 97.26%, aligning closely with ideal ranges for injectable biomaterials. Density measurements indicated that all samples approximated or exceeded the minimum density of healthy bone, with Sample C reaching 1.18 g/cm³. pH monitoring over 21 days revealed a consistent value of ~6, suggesting good chemical stability. These results demonstrate that the 15% PVA formulation achieves an optimal compromise between physicochemical properties and clinical applicability. This composite's injectability enables precise defect filling and promotes new bone formation, making it a superior and promising alternative as an injectable bone graft material in patients.